Increasing Awareness of a Provincial Mental Health Resource for Boys and Young Men 12 to 17 Years: Reflections From Foundry's Province-Wide Campaign. Issue 5 (September 2020) - Zenone, Marco; Irving, Paul; Cianfrone, Michelle; Lockhart, Leah; Costales, Stefanie; Cruz, Kathryn; Ignacio, Jamie
Foundry empowers youth and young adults aged 12 to 24 years to lead healthy lives through a province-wide network of centers and online resources in British Columbia, Canada. However, initial evaluation data gathered from Foundry centers have shown that boys and young men are half as likely to access Foundry compared to girls and young women. To address this need, we set out to understand why boys and young men aged 12 to 17 years aren't accessing mental health supports and to develop a promotional campaign to connect them with the resources available through Foundry. A campaign concept called "Everything Is Fine" was chosen; the campaign depicts boys and young men trying to appear as if they are OK, even though their facial expressions clearly show they are holding back stress. The campaign concept was chosen through an iterative process of research and testing. Promotion materials were created for social media (Instagram, Snapchat) and school posters, which were distributed across British Columbia, Canada . Evaluation was conducted through social media analytics and google analytics. Pre- and postsurveys were also distributed to two school districts to assess recognition of Foundry. Approximately 160, 000+ persons viewed the media on Instagram, while 170, 000+ viewed on Snapchat. There was a 70% increase in website traffic compared with the 3 months prior (18, 881 vs. 11, 126). In the surveyed school districts, Foundry awareness increased by 10% and 15%. The lessons learned from our campaign were to prioritize research and to leverage media agency experience for large campaigns.